2012
DOI: 10.1242/jcs.102061
|View full text |Cite
|
Sign up to set email alerts
|

Polycomb repressive complex 2 impedes intestinal cell terminal differentiation

Abstract: SummaryThe crypt-villus axis constitutes the functional unit of the small intestine, where mature absorptive cells are confined to the villi, and stem cells and transit amplifying and differentiating cells are restricted to the crypts. The polycomb group (PcG) proteins repress differentiation and promote self-renewal in embryonic stem cells. PcGs prevent transcriptional activity by catalysing epigenetic modifications, such as the covalent addition of methyl groups on histone tails, through the action of the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
54
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 41 publications
(63 citation statements)
references
References 68 publications
8
54
1
Order By: Relevance
“…The cells were treated with 1 µM RA or vehicle in the growth medium for 6 days and counted using a cell and particle counter (Coulter Z; Beckman Coulter, Inc., Fullerton, CA). Stable Suz12 knockdown (shRNA sequence TRCN0000038728) and control cell populations were established as described [25]. …”
Section: Methodsmentioning
confidence: 99%
“…The cells were treated with 1 µM RA or vehicle in the growth medium for 6 days and counted using a cell and particle counter (Coulter Z; Beckman Coulter, Inc., Fullerton, CA). Stable Suz12 knockdown (shRNA sequence TRCN0000038728) and control cell populations were established as described [25]. …”
Section: Methodsmentioning
confidence: 99%
“…Typical cell markers identified in the lower crypt in the intact intestine are also expressed in HIEC cells including adhesion and signaling molecules [6163], metabolism [64] and inflammatory response [65,66]. Furthermore, while HIEC cells are undifferentiated, studies have shown that reintroduction of the intestine-specific pro-differentiation factors CDX2, HFN-1α and GATA-4 can induce enterocytic differentiation [67,68]. Taken together, HIEC cells represent a valid human intestinal crypt cell model.…”
Section: Methodsmentioning
confidence: 99%
“…Conditional deletion of Ezh2, for example, in B cells (Su et al, 2003), neuronal stem cells (Hirabayashi et al, 2009;Pereira et al, 2010), epidermal progenitors (Ezhkova et al, 2011;Ezhkova et al, 2009;Lien et al, 2011) and pancreatic islet b cells (Chen et al, 2009) has provided insights into the function of PRC2 within lineage restricted somatic cells. However, the differing phenotypes within these studies indicate that Ezh2 action may be highly dependent on the differentiation stage of the stem cell and may even regulate the differentiation programme (Benoit et al, 2012). Interestingly, loss of Ezh2 within cardiac progenitors leads to an upregulation of Six1 dependent skeletal muscle genes (Delgado-Olguín et al, 2012), suggesting that Ezh2 may not only be required for stem cell function but may also act to ensure the correct lineage choice of a stem cell.…”
Section: Introductionmentioning
confidence: 97%